2015
DOI: 10.5032/jae.2015.02170
|View full text |Cite
|
Sign up to set email alerts
|

Professional Development Needs of Beginning Agricultural Education Teachers in Idaho

Abstract: The continuing shortage of agricultural education instructors has been documented across the state and nation. Secondary instructor retention may help reduce the shortage and position changes each year. Identifying the challenges facing beginning teachers as perceived by beginning teachers, veteran teachers, and building administrators can help identify the professional development and mentoring needs to assist in teacher retention. Establishing consensus among the target groups through this Delphi study will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…Barrick et al (1983) conducted the first needs assessment of agricultural education teachers found in the literature base. More recently, a needs assessment of Idaho agricultural education teachers was conducted by Touchstone (2015). Davis and Jayaratne (2015) conducted a study which focused on preparing agriculture teachers for the 21 st century.…”
Section: Purpose and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Barrick et al (1983) conducted the first needs assessment of agricultural education teachers found in the literature base. More recently, a needs assessment of Idaho agricultural education teachers was conducted by Touchstone (2015). Davis and Jayaratne (2015) conducted a study which focused on preparing agriculture teachers for the 21 st century.…”
Section: Purpose and Objectivesmentioning
confidence: 99%
“…The areas of developing knowledge and skills in plant sciences and animal sciences, conducting parent/teacher conferences, and planning and conducting student field trips were indicated as lower priority needs for in-service (Duncan et al, 2006;Joerger, 2002;Layfield & Dobbins, 2002). In a more recent study, Touchstone (2015) found funding and long-term planning and prioritization as an overall high need in Idaho. Layfield and Dobbins (2002) found preparing FFA degree applications, organizing FFA fundraisers, and supervising SAE programs were mentioned as high priority in-service needs of South Carolina agricultural education teachers.…”
Section: Needs Assessments For Sbae Teachers From 2000 To 2015mentioning
confidence: 99%
“…Similar to a plethora of previous agricultural education Delphi studies (Breeding, Rayfield, & Smith, 2018;Easterly & Myers, 2017;Lundry, Ramsey, Edwards, & Robinson, 2015;Touchstone, 2015), the three-round Delphi technique was used. A total of three Delphi instruments were used to collect data, one for each round.…”
Section: Data Collectionmentioning
confidence: 99%
“…These areas of lower perceived preparedness coincide with previous findings. For example, Touchstone (2015) reported program funding and recruiting students were program areas of concern for beginning teachers in Idaho.…”
Section: Objectivementioning
confidence: 99%